The Effect of Loquat Fruit (Eriobotrya japonica) Marmalade Addition and Storage Time on Phsico-Chemical and Sensory Properties of Yogurt - Hasan Temiz (Journal of Agricultural Sciences)
The objective of this study was to investigate the physico-chemical and sensorial changes during storage period in yogurts that were manufactured by adding loquat fruit (Eriobotrya japonica) marmalade at 4 different ratios (5%, 10%, 15%, 20%). The pH and yellowness/blueness (b*) values of yogurts increased with increasing marmalade ratios, whereas titratable acidity, viscosity, syneresis, redness (a*) and lightness (L*) values decreased. The pH and viscosity values of the yogurts decreased continuously through storage. Yogurts containing loquat marmalade were overall acceptable in terms of sensory characteristics. The production of fruit flavoured yogurts by adding 15% marmalade would be recommended.